Eyes and speech in English, Finnish and Czech children’s literature - Čermáková, Anna; Malá, Markéta (Bergen Language and Linguistics Studies, 2021)
This study explores cross-linguistically, in English, Czech and Finnish, eye-behaviour that occurs in children’s fiction in the vicinity of character speech. We explore how authentic eye behaviour, as an important part of non-verbal communication, is rendered in fictional worlds. While there are more similarities than differences across the languages in the characteristics and narrative functions of fictional eye-behaviour, the linguistic encoding differs substantially due to typological differences between the languages. The same semantic roles are often expressed by divergent syntactic means. The divergence is reflected primarily in the relative weight of different word-order principles, the different means of indicating simultaneity, as well as the role of inflection in Finnish and Czech.